LOCAL ARMED FORCES AND PRISONERS OF WAR IN THE TURKESTAN MILITARY DISTRICT DURING THE FIRST WORLD WAR (Scientific journal of the Fergana State University, 2025)
This article analyzes the participation of the Russian Empire and the Turkestan Military District within it in the First World War in 1914-1918. The main focus of the article is on the fate of the local armed forces formed in Turkestan and participating in the World War and the German and Austro-Hungarian prisoners of war placed in Turkestan.